Chitinolytic Bacteria Isolated from Chili Rhizosphere: Chitinase Characterization and Application as Biocontrol for Aphis gossypii (Microbiology Indonesia, 2010)
Chitin, a common constituent of insect exoskeleton, could be hydrolyzed by chitinase. This research was conducted to select rhizobacteria isolated from the rhizosphere of chili pepper that produced chitinase and to examine their chitinase activity in degrading chitin of the Aphis gossypii. A total of 25 rhizobacteria isolates formed a clear zone when grown on chitin agar. Three of them had the highest chitinolytic index and were identified as Bacillus sp. strain I.5, I.21, and II.14. The II.14 was chosen for characterization of chitinase activity. The isolate showed maximum chitinase activity at 48-h-incubation. Maximum temperature and pH of the chitinase activity were 55°C and 7.0, respectively. The cell culture and the enzyme crude extract of the above three isolates were tested against A. gossypii and the result was compared to the control through microscopic observation. Hydrolytic analysis showed that the enzyme crude extract of these isolates were able to degrade chitin of insect exoskeleton since the first 3-h-incubation. Meanwhile, the cell culture treatment on the chitin showed degrading activity after 12 h (Bacillus sp. strain I.21 and II.14), and 9 h (Bacillus sp. strain I.5). Chitin degradation of A. gossypii exoskeleton by enzyme crude extract was better than the cell culture treatment. Chitinases produced by Bacillus sp. strains I.5, I.21, and II.14 are potential as biocontrol agents for A. gossypii.